Efektifitas Promosi UPH Tahun 2003 - Suratmo, Lol Joko (Faculty of Social and Political Science - Universitas Pelita Harapan, 2004)
Promotion is one of the technique which been used in many university to get student every semester. What is promotion ? Promotion in this paper is all the activities which aim to get student, through advertising, personal selling, sales promotion, publicity, and Marketing Public Relations. Â This paper was taken from the research about the The Effectiveness of UPH activities to get FISIP 2003 Student. The tool which been used in this research was survey research ; which collected data from FISIP 2003 students. Through all the 2003 student we trying to find about all the information they get about UPH and which Promotion activies they used to make decision get into FISIP UPH. From this research we found that personal selling was the effective way (86,9%) to get a new students; better than other promotion activities.